Polyurethane Microstructures-a Good or Bad in vitro Partner for the Isoflavone Genistein? - Danciu Corina (NATURAL PRODUCT COMMUNICATIONS, 2015)
In recent years polyurethane microstructures (PM) have gained increasing attention in the pharmaceutical field due to the importance of their practical application. Since finding that such a formulation with genistein could improve its applications, we have conducted a preliminary study regarding the in vitro antiproliferative (MCF7, MDA-MB-231 and T47D) and antimicrobial (Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella enteritidis (D), Bacillus subtilis, B. cereus, and Candida albicans) activity in order to test whether polyurethane micro structuresre present a good option for further modulation of genistein's bioavailability. It was concluded that the polyurethane micro structures are a bad in vitro partner for the isoflavone genistein.